The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep41716
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Sensing Properties of Spin-coated Na-doped ZnO Nanostructured Films

Abstract: In this report, the structures, morphologies, optical, electrical and gas sensing properties of ZnO and ZnO: Na spin-coated films are studied. X-ray diffraction (XRD) results reveal that the films are of a single phase wurtzite ZnO with a preferential orientation along (002) direction parallel to c-axis. Na doping reduces the crystalline quality of the films. The plane surface of ZnO film turned to be wrinkle net-work structure after doping. The reflectance and the optical band gap of the ZnO film decreased af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(80 citation statements)
references
References 60 publications
1
79
0
Order By: Relevance
“…The band gap of the sprayed films is calculated using Tauc's relation using the following equation: (normalαnormalhnormalv)2=Btrue(hvEgtrue) where α , B , and Eg are the absorption coefficient, proportionality constant, and optical band gap; respectively, the absorption coefficient is calculated by the following equation: α=2.303At where A and t are the absorbance and thickness, respectively, Figure shows the band gap of pure and Ba‐doped Mn 3 O 4 thin films, the values fairly agree with the work reported in literature . It is found that band gap varies as Ba concentration increases reaching a minimum value 2.85 eV in Mn 3 O 4 :Ba1% thin films, the reduction in band gap may be due to the increase in RMS roughness and crystallite size as reported earlier, it is also observed band gap decreases with the increase in unit cell volume as well as bond lengths of (Mn 2+ O) and (Mn 3+ O) in tetrahedral and octahedral sites; respectively (see Table ) as Ba concentration increases, this behavior agrees with the findings reported in literature …”
Section: Resultssupporting
confidence: 54%
“…The band gap of the sprayed films is calculated using Tauc's relation using the following equation: (normalαnormalhnormalv)2=Btrue(hvEgtrue) where α , B , and Eg are the absorption coefficient, proportionality constant, and optical band gap; respectively, the absorption coefficient is calculated by the following equation: α=2.303At where A and t are the absorbance and thickness, respectively, Figure shows the band gap of pure and Ba‐doped Mn 3 O 4 thin films, the values fairly agree with the work reported in literature . It is found that band gap varies as Ba concentration increases reaching a minimum value 2.85 eV in Mn 3 O 4 :Ba1% thin films, the reduction in band gap may be due to the increase in RMS roughness and crystallite size as reported earlier, it is also observed band gap decreases with the increase in unit cell volume as well as bond lengths of (Mn 2+ O) and (Mn 3+ O) in tetrahedral and octahedral sites; respectively (see Table ) as Ba concentration increases, this behavior agrees with the findings reported in literature …”
Section: Resultssupporting
confidence: 54%
“…The lowest detectable concentration of explosive is restricted by the fabricated setup and depending on the value of noise. The sensor noise is computed from the recorded changes in the relative resistance of the baseline via the root‐mean‐square deviation or rms . truenormalVX2=Σ4pt(ynormali-y)2 …”
Section: Resultsmentioning
confidence: 99%
“…For example, Shaban used Na-doped ZnO nanostructures for enhanced CO 2 detection, and Saraswathi demonstrated that DC magnetron sputtered films of polycrystalline ZnO can be used for highly sensitive humidity sensors 6, 7 . Although the environmental effects on the electrical properties of ZnO films are well studied, the response mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%